Understanding the Dark Sides of Alternative Economies to Maximize Societal Benefit. (June 2020) - Watson, Forrest; Ekici, Ahmet
Alternative economies can significantly contribute to societal flourishing, but the potential dark sides should also be considered. As shared commitments are the foundation of alternative economies, we draw on related literature to conceptualize various types of dark sides of an alternative economy. While less prominent than the well-being outcomes, we present qualitative data of when the participants of one alternative food network experienced disappointment, burnout, guilt, or division. Comparing with the dark sides gleaned from other studies on alternative economies, we present a framework for evaluating the dark sides in alternative economies. Dark sides can be on a continuum from the micro level to the macro level, as well as more likely to threaten the continuance of alternative economies or societal well-being. We offer recommendations to guard against the vulnerabilities of alternative economies for their continued growth and impact, as well as discuss the implications for research on marketing systems failure.